2021
DOI: 10.1371/journal.pone.0254536
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the influence of cell concentration in design and development of microbially induced calcium carbonate precipitation (MICP) process

Abstract: Microbially induced calcium carbonate precipitation (MICP) process utilising the biogeochemical reactions for low energy cementation has recently emerged as a potential technology for numerous engineering applications. The design and development of an efficient MICP process depends upon several physicochemical and biological variables; amongst which the initial bacterial cell concentration is a major factor. The goal of this study is to assess the impact of initial bacterial cell concentration on ureolysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…For a cell suspension with OD 600 = 0.15 they found the largest crystals with a volume of 8000 µm 3 , for a cell suspension of OD 600 = 1.3 only crystals with a volume of 400 µm 3 . These results are in accordance with the findings of Konstantinou et al ( 2021b ), Heveran et al ( 2019 ) and Murugan et al ( 2021 ) all of whom found an antiproportional relationship between the urease activity and therefore the OD of an organism and the size of CaCO 3 crystals formed. Except the study of Konstantinou et al ( 2021b ) these studies did not differentiate between biomass concentration and ureolytic activity.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…For a cell suspension with OD 600 = 0.15 they found the largest crystals with a volume of 8000 µm 3 , for a cell suspension of OD 600 = 1.3 only crystals with a volume of 400 µm 3 . These results are in accordance with the findings of Konstantinou et al ( 2021b ), Heveran et al ( 2019 ) and Murugan et al ( 2021 ) all of whom found an antiproportional relationship between the urease activity and therefore the OD of an organism and the size of CaCO 3 crystals formed. Except the study of Konstantinou et al ( 2021b ) these studies did not differentiate between biomass concentration and ureolytic activity.…”
Section: Introductionsupporting
confidence: 93%
“…For the application of Sporosarcina pasteurii and other ureolytic microorganisms with intracellular urease, the biomass concentration and the urease activity are parameters that cannot influence MICP separately from each other. A higher biomass concentration and thus urease activity, leads to an increased degradation of urea and thus to a faster formation of carbonate ions, which in turn favors a faster CaCO 3 precipitation (Murugan et al 2021 ). However, the use of higher urease activities promotes the formation of smaller CaCO 3 crystals, which in turn may have a negative effect on the consolidation of sand (Cheng et al 2017 ; Wang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a linear relationship between the initial urea decomposition rate and cell concentration in the earliest reports [ 67 ]. It was influenced by the control of single-cell kinetics and the maximum critical initial cell concentration [ 68 ]. Hommel [ 69 ] improved the calibration of the model under the consideration of the effects of carbonate precipitation and concentration on urea decomposition to enhance the applicability to MICP.…”
Section: Mineralization Technologymentioning
confidence: 99%
“…The main factors that can impact microbially induced carbonate precipitation are bacterial genotype and cell concentration, appropriate amounts of Ca 2+ (supplemented externally) and urea (for CO 3 2− production), nutritional composition of medium for bacteria cultivation, and pH conditions for urease activity [ 28 , 29 , 30 ]. Likewise, the availability of crystal nucleation sites was found to greatly affect the calcium attachment, and finally, the formation of calcium carbonate crystals [ 31 ], although “the mechanism that controls the growth and crystallization process remains unclear and controversial” [ 32 ].…”
Section: Introductionmentioning
confidence: 99%